MEDIA REALIA BAGI SISWA SMK - HERYNA, VIO RAMADHANTY; Yulistiana, Yulistiana (Jurnal Online Tata Busana, 2021)
Realia media is an object that can be heard, seen or experienced that causes students to have hands-on experience among them for vocational school students in all skill programs. The purpose of this literature study is to find out: 1) characteristics of realia media, 2) the response of learners to realia media, 3) the results of learning learners using realia media. This literature study examines the results of research on the application of realia media in vocational schools. The data search in this article uses Google Scholar and Scient Direct obtained as many as 10 articles in 2012-2018. The results of the analysis of this literature study are: 1) The characteristics of real media are real objects, objects that are still in intact condition, can be used, alive, at real size, and can be recognized as their original form, can be living objects and inanimate objects. 2) The response of students is very good to learning using realia media that is proven by the understanding and ability of learners when doing tasks. 3) The results of learning students using realia media, it is obtained an increase in student learning outcomes by 25%-100% whose maximum value is 9 and an average of 7.5. Keywords: Learning outcomes, realia media, student response, vocational students.